(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The bilingual experience can be explored through various lenses, such as sociolinguistics, psycholinguistics, and cultural studies. Researchers can examine how bilinguals negotiate their identity through language use, how they switch between languages in different contexts, and how their language identity evolves over time. The study concludes that since language contains a common worldview and cultural meanings for native speakers, linguistic identity is also usually built through the language that is most often used in a person’s daily life and the degree of proficiency, in turn, is related to the use of the language. Consequently, the degree of language proficiency improves the more the language is used.